Regularization-based independent control of an external electromagnetic actuator to avoid singularity in the spatial manipulation of a microrobot. (April 2020) - Nguyen, Kim Tien; Hoang, Manh Cuong; Go, Gwangjun; Kang, Byungjeon; Choi, Eunpyo; Park, Jong-Oh; Kim, Chang-Sei
Abstract: This paper proposes a regularization-based independent electromagnetic field control methodology of an external electromagnetic actuator (EMA) for untethered medical microrobot manipulation. The EMA developed in this study consists of six stationary air-filled coils in an orthogonal configuration to generate a 3-dimensional (3-D) gradient magnetic field. Each air-cored coil is considered as a magnetic dipole actuator and independently control it with other coils. However, the independent electromagnetic coil controller derived by a linear combination of magnetic fields often causes an unexpected singularity problem while obtaining input current via inverse electromagnetic field models. This results in a power overshoot and uncontrollable motion of a micro-object along specific orientations in 3-D space. Hence, a novel control approach based on the regularization of singular value decomposition (SVD) is proposed to solve the singularity problem while providing the optimal current input to electromagnets. Initially, electromagnetic field models are derived, simulated, and analyzed for controller design. In the next stage, the regularization-based independent coil controller is obtained numerically and verified experimentally. These methods enable spatial manipulation of a micro-object using six stationary electromagnets in an electromagnetic navigation system (ENS) with enough force and avoids singularity. Simulations and experiments were conducted and could verify the effectiveness of the proposed control method by avoiding singularities in magnetic field control with minimum number of coils.